1960
DOI: 10.1113/jphysiol.1960.sp006480
|View full text |Cite
|
Sign up to set email alerts
|

The effect of semistarvation on absorption by the rat small intestine in vitro and in vivo

Abstract: During a period of semistarvation there is a fall in the mass of body cells and a lowering of the basal metabolic rate (Wishart, 1934;Taylor & Keys, 1950;Grande, Anderson & Keys, 1958), the degree to which each change occurs depending upon the duration of the experiment and the severity of the dietary restriction. The loss of cellular mass and the fall in the metabolic rate depend upon the number of calories available, and provided that the caloric restriction is not too severe an equilibrium situation can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
47
0
2

Year Published

1967
1967
1978
1978

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(53 citation statements)
references
References 17 publications
4
47
0
2
Order By: Relevance
“…It is of interest, therefore, that the absorptive capacity of the small intestine of the rat and mouse is enhanced, rather than decreased, for. some nutrients such as D( + )-glucose after the imposition of a severe decrease in intake of a balanced food (Kershaw et al 1960;Hindmarsh et al 1967;Madge 1970) and the present work shows that this response is retained even when the animals have lost 40 % of body weight. Although there will always be difficulties in extrapolating data from one species to another, it seems valuable to pursue the influence of variable dietary deprivation at different ages and for different periods of time on digestive function in the rat because some principles may emerge which are applicable across species.…”
mentioning
confidence: 58%
See 2 more Smart Citations
“…It is of interest, therefore, that the absorptive capacity of the small intestine of the rat and mouse is enhanced, rather than decreased, for. some nutrients such as D( + )-glucose after the imposition of a severe decrease in intake of a balanced food (Kershaw et al 1960;Hindmarsh et al 1967;Madge 1970) and the present work shows that this response is retained even when the animals have lost 40 % of body weight. Although there will always be difficulties in extrapolating data from one species to another, it seems valuable to pursue the influence of variable dietary deprivation at different ages and for different periods of time on digestive function in the rat because some principles may emerge which are applicable across species.…”
mentioning
confidence: 58%
“…Experimental studies in the rat have shown enhanced absorptive capacity of the small intestine for some nutrients after dietary restriction had resulted in up to 23 % body weight loss (Kershaw et al 1960;Hindmarsh et al 1967). Jackson (1925) reported that young adult mammals, such as the rats used in the above experiments, are capable of losing about 50 % of their body weight before death.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is expected that the small intestinal function is reflected partly by the mature cell number existing on the villi. Many investigators have observed the effect of diet on the cell renewal or the digestive and absorptive functions (1)(2)(3)(4). However there has been little research to examine the relationship between cell renewal and the functions.…”
Section: Discussionmentioning
confidence: 99%
“…Chez les mammifères, l'influence du régime alimentaire sur la vitesse d'absorption des acides aminés fait l'objet de nombreux travaux depuis que Neame et Wiseman (1959) puis Kershaw, Neame et Wiseman (1960) ont montré que la restriction éner-gétique entraîne chez le rat une augmentation du transport actif de l'histidine.…”
Section: Introductionunclassified